Study of Thyroid Abnormalities using Scintigraphy - Ahmed, Amel Bushra; Yousef, Mohamed; Fadhlalah, Salah Ali (British Journal of Healthcare and Medical Research, 2018)
Radionuclide imaging is an integral part of functional evaluation of thyroid diseases. This study aimed to study thyroid abnormalities using scintigraphy, The study population consisted of 173(149 female and 24 male) patients with thyroid abnormalities, and referred to Nuclear Medicine, Fujairah hospital for thyroid scintigraphy during the period from Jan 10, 2016 to June 30, 2018. All patients Thyroid function test were done before coming to radiology department. The mean age of patients was 38 years. The results of this study revealed that thyroid nuclear medicine scan findings as normal in 6.4 % (16 patients) and abnormal in 91% (157 patients) , Autonomous Nodule 2 (1.1),nodular goiter- NTG , TNG 30 (17.3%),Goiter11(6.4%),Grave disease13(7.5%), Multinodular goiter 43(24.8%), Thyroiditis 20 (11), Thyroid nodule 2 (1.1), Toxic multinodular goiter 21 ,Toxic goiter 15 (8.7%), Normal 16 (9.2%). This study concluded that radionuclide methods are complementary and provide information that can help in the appropriate management of various thyroid diseases.